Recombinant Bacteriocin Rhamnosin Suppresses Malignant Phenotypes of Colorectal Cancer Cells - Tantimetta, Phonprapavee; Rattanaarchanai, Thanakrit; Aroonkesorn, Aratee; Chanket, Wannarat; Runsaeng, Phanthipha; Roytrakul, Sittiruk; Hutamekalin, Pilaiwanwadee; Obchoei, Sumalee (Trends in Sciences, 2025)
Colorectal cancer (CRC), the third most diagnosed cancer worldwide, is believed to worsened by microbiome dysbiosis, which promotes carcinogenesis through inflammation and genetic instability. Lactic acid bacteria (LAB), known for their beneficial metabolites, produce bacteriocins with potential anticancer properties. Here we hypothesized that recombinant rhamnosin (rRN), derived from the prebacteriocin gene of Lactobacillus rhamnosus, may inhibit CRC progression by targeting oncogenic pathways associated to proliferation, metastasis, and chemoresistance. We evaluated the anticancer activity of rRN in HT-29 and Caco-2 CRC cells, along with normal oral keratinocyte (NOK-SI) cells, using cell viability (MTT assay), apoptosis (Hoechst/propidium iodide dual nuclear staining), migration and invasion (Boyden chamber assay), and RT-qPCR to measure the expression of genes regulating growth, motility, and drug resistance. The results revealed that rRN dose-dependently inhibited CRC cell viability (IC50: 25.3 and 14.5 µg/mL for HT-29 and Caco-2, respectively) with minimal toxicity to NOK-SI cells (IC50: >32 µg/mL). When combined with 5-fluorouracil (5-FU), it enhanced the growth inhibitory effect. rRN induced apoptosis and suppressed migration and invasion by 70 - 80 %. Transcriptional profiling revealed the downregulation of genes related to cell growth (CCNB1, CCND1 and EGFR), motility (FN1, PXN and SNAI1), and drug resistance (ABCG2, MRP1 and MRP2), while CCNE1 and VIM remained unaffected, underscoring rRN’s selective targeting of CRC progression pathways. These findings establish rRN as a multitarget therapeutic candidate for CRC, addressing proliferation, metastasis, and chemoresistance - key challenges in CRC relapse. Future studies should validate protein-level mechanisms, such as caspase activation and BCL-2/Bax dynamics, and evaluate rRN’s efficacy in preclinical models. This work underscores the potential of rRN, a LAB-derived bacteriocin, as a novel adjuvant for CRC treatment. HIGHLIGHTS Gut microbiome imbalance promotes colorectal cancer (CRC) development, while lactic acid bacteria (LAB) produce beneficial bacteriocins with potential anticancer properties. This study produced recombinant rhamnosin (rRN), derived from the prebacteriocin gene of Lactobacillus rhamnosus, a type of LAB. rRN exhibits anticancer effects by inhibiting CRC cell proliferation, enhancing chemosensitivity, inducing apoptosis, and suppressing migration and invasion. rRN modulates oncogenic pathways by downregulating genes associated with cell growth (CCNB1, CCND1 and EGFR), motility (FN1, PXN and SNAI1), and drug resistance (ABCG2, MRP1 and MRP2). GRAPHICAL ABSTRACT